Perspective On Excellence in Forensic Mental Health Services: What We Can Learn From Oncology and Other Medical Services - Kennedy, Harry G.; Simpson, Alexander; Haque, Quazi (Frontiers in Psychiatry, 2019)
We propose that excellence in forensic and other mental health services can be recognised by the abilities necessary to conduct randomised controlled trials (RCTs) and equivalent forms of rigorous quantitative research to continuously improve the outcomes of treatment as usual (TAU). Forensic mental health services (FMHS) are growing, are high cost and increasingly provide the main access route to more intensive, organised and sustained pathways through care and treatment. A patient newly diagnosed with a cancer can expect to be enrolled in RCTs comparing innovations with the current best TAU. The same should be provided for patients newly diagnosed with severe mental illnesses and particularly those detained and at risk of prolonged periods in a secure hospital. We describe FMHS in four levels 1 to 4, basic to excellent according to seven domains: values or qualities of clinical organisation, consistency, timescale, specialisation, routine outcome measures and research. Excellence is not elitism. Not all centres need achieve excellence, though all should be of high quality. Services can provide each population with a network of centres with access to one centre of excellence. Excellence is the standard needed to drive the virtuous circle of research and development that is necessary for teaching, training and the pursuit of new knowledge. Substantial advances in treatment of severe mental disorders requires a drive at national and international level to create services that meet these standards of excellence and are focused, active and productive to drive better functional outcomes for service users.